The working mechanisms of low molecular weight polynaphthalene sulfonate superplasticizers. (20th April 2020) - Mezhov, Alexander; Ulka, Simon; Gendel, Youri; Diesendruck, Charles E.; Kovler, Konstantin
Highlights: All PNS types up to critical dosage demonstrate the same adsorption behavior and zeta potential development. At the critical dosage dispersing ability is governed by the increment of zeta potential value. Above the critical dosages, the plasticizing effect is governed by both increment in surface charge and air content. Above the saturation dosages, air content changes are not significant, while the amount of non-adsorbed polymer increases. The polymer with lowest molecular weight retards hydration the most. Abstract: Polynaphtalene Sulfonate (PNS) superplasticizers are one of the most commonly used admixtures in concrete production. Yet, PNS working mechanism has been studied in the context of the effect it has on individual properties, limiting the overall understanding of the parallel effects this admixture creates. This study connects the microscopic behavior of PNS of different molecular weights to their effect on the macroscopic properties of the cementitious system, including dispersing ability, air entrainment and retardation as a consequence of the molecular adsorption on cement and free PNS in solution. Our results confirmed that changes in macroscopic properties are not only a consequence of the adsorbed polymer but also of the non-adsorbed, which in turn reduces paste viscosity due to an increment in air entrainment. The induction period at the low dosage is equal for all polymers, while at the high dosage polymer with the lowest molecular weight retards hydration the most.